Studies on competition between wheat and Chenopodium album L. (Bangladesh Journal of Agricultural Research, 2007)
A field experiment was conducted at the Agronomy Field of Bangladesh Agricultural University (BAU), Mymensingh during the period from November 2001 to March 2002 to investigate the effect of Chenopodium album competition on growth and yield of wheat and to determine the critical period of weed (C. album) competition in wheat. The experiment was consisted of 7 treatments viz., weed free for whole crop life, weed competition (WC) for 20, 40, 60, and 80 days after emergence (DAE), WC for 110 DAE (no weed control) and weed monoculture. The highest grain yield (3.95 t/ha) was obtained from weed free and that of the lowest from weedy (2.65 t/ha) condition. Grain yield decreased gradually with the increase in weed competition duration. Wheat yield reductions due to C. album competition for 20, 40, 60, 80, and 110 DAE were 12.65, 28.10, 29.11, 31.64, and 32.9 %, respectively. The highest rate of yield decrease was in between 20 and 40 DAE. The highest reduction of wheat yields under weedy check treatment (32.91% grain and 33.75% straw) were the results of 31.0 % reduction of total tillers/plant, 43.34% reduction of effective tillers/plant, 14.57% reduction of grains/spike, 34.5% reduction of total dry weight of wheat. The plant height of C. album was reduced due to wheat competition by 32.3% and that of total dry matter by 34.2 %. The critical period of weed competition lies between 20 and 40 DAE. Bangladesh J. Agril. Res. 32(2) 2007: 191-203.